Pengaruh Kemudahan dan Keamanan Terhadap Minat Penggunaan Pembayaran Non Tunai Quick Reaponse Code Indonesian Standart (QRIS) dalam perspektif Maqashid Syariah - Aldi Adfa Sholeh; Miftahul Hasanah; Siti Khayisatuzahro Nur (STAI Al-Mas'udiyah, 2025)
This study aims to examine the extent to which ease of use and security affect the interest in using a non-cash digital payment system based on the Quick Response Code Indonesian Standard (QRIS) among MSMEs in Jember Regency, viewed from the perspective of Maqashid Syariah. This study adopts a quantitative approach with an associative research type. The research sample consisted of 100 respondents selected by purposive sampling from the population of MSMEs using QRIS. Data analysis used multiple linear regression with the help of the SPSS version 25 program. The results showed that the ease of use variable (X1) had a positive and significant effect on the interest in using QRIS, as evidenced by a significance value of 0.000 <0.05 and a T value of 6.905. Likewise, the security variable (X2) showed a significant effect with a significance value of 0.000 and a t value of 3.946 and a level. Simultaneously, both variables had a significant effect on the interest in using QRIS, supported by the results of the F test of 76.963 with a significance value of 0.000. From the perspective of Maqashid Syariah, QRIS supports five main aspects, namely protection of religion (Hifz al-Din), life (Hifz al-Nafs), reason (Hifz al-‘Aql), property (Hifz al-Mal), and descendants (Hifz al-Nasl). QRIS is considered to be able to encourage efficiency, security, and transparency in financial transactions, while being in line with Islamic ethical values ​​and principles.